2020
DOI: 10.1002/jcp.29495
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐targeted antioxidant mito‐TEMPO alleviate oxidative stress induced by antimycin A in human mesenchymal stem cells

Abstract: The cell therapy of damaged tissue, which is linked to hypoxia condition might fail, in large part due to the emergence of oxidative stress (OS) and/or mitochondrial dysfunctions. Thus, the invigoration of stem cells against oxidative stress could be a reliable strategy to improve the cell therapy outcome. Of various antioxidants, mito‐Tempo (mito‐T) is one of the potent antioxidants that could target and neutralize the mitochondrial oxidative stress. In this study, for the induction of hypoxia and oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Nrf2 is a transcription activator that attaches to the antioxidant response elements in the promoter regions of target antioxidant genes and is critical for the harmonized up-regulation of genes in response to oxidative stress. 20 As shown in Fig. 7 , a decreased profile level of Nrf2 was detected in the cells nested at the CS scaffold ( P = 0.003).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Nrf2 is a transcription activator that attaches to the antioxidant response elements in the promoter regions of target antioxidant genes and is critical for the harmonized up-regulation of genes in response to oxidative stress. 20 As shown in Fig. 7 , a decreased profile level of Nrf2 was detected in the cells nested at the CS scaffold ( P = 0.003).…”
Section: Resultsmentioning
confidence: 70%
“…Decreased oxidative stress leads to MSCs' promoted proliferation besides DNA stability. 20 , 21 Despite high contents of glutathione and an active antioxidant system in MSCs, they endure ROS production as they replicate. Elevated levels of ROS lead to a decreased cell differentiation though in adipose tissue, it is the opposite.…”
Section: Introductionmentioning
confidence: 99%
“…In the very low tension of oxygen, 0.5% (anoxia), oxidative stress will be induced and ATP production will be disrupted and the cells will undergo the apoptosis (Barzegari, Nouri, et al, 2020; Guzy & Schumacker, 2006). However, under hypoxia (0.5%–3% O 2 ), physiological ROS production is vital for the bio‐function of stem cells.…”
Section: Hypoxia‐induced Ros In Biology Of Stem Cellsmentioning
confidence: 99%
“…A vast progress in stem cell therapy has held great promise for regenerative medicine; yet, it is limited due to the poor homing and survival of transplanted stem cells owing to higher physiological stresses specially hypoxia‐induced oxidative stress (Barzegari, Nouri, et al, 2020). Transplanted stem cells face an unfavorable environment with low oxygen and nutrient (Abdollahi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Barzegari et al (2020) reported that the mitochondria‐targeted antioxidant mito‐TEMPO activates Nrf2. ( 5 ) However, the contribution of Nrf2 to the regulation of mitochondrial oxidant stress in APAP‐induced liver injury remains unclear and warrants further study.…”
mentioning
confidence: 99%